Estrogen receptor subtypes dictate the proliferative nature of the mammary gland. Issue 3 (June 2018) - Dall, Genevieve V; Hawthorne, Samuel; Seyed-Razavi, Yashar; Vieusseux, Jessica; Wu, Wanfu; Gustafsson, Jan-Ake; Byrne, David; Murphy, Leigh; Risbridger, Gail P; Britt, Kara L
Abstract : Estrogen induces proliferation of breast epithelial cells and is responsible for breast development at puberty. This tightly regulated control is lost in estrogen-receptor-positive (ER+) breast cancers, which comprise over 70% of all breast cancers. Currently, breast cancer diagnosis and treatment considers only the α isoform of ER; however, there is a second ER, ERβ. Whilst ERα mediates estrogen-driven proliferation of the normal breast in puberty and breast cancers, ERβ has been shown to exert an anti-proliferative effect on the normal breast. It is not known how the expression of each ER (alone or in combination) correlates with the ability of estrogen to induce proliferation in the breast. We assessed the levels of each ER in normal mouse mammary glands subdivided into proliferative and non-proliferative regions. ERα was most abundant in the proliferative regions of younger mice, with ERβ expressed most abundantly in old mice. We correlated this expression profile with function by showing that the ability of estrogen to induce proliferation was reduced in older mice. To show that the ER profile associated with breast cancer risk, we assessed ER expression in parous mice which are known to have a reduced risk of developing ERα breast cancer. ERα expression was significantly decreased yet co-localization analysis revealed ERβ expression increased with parity. Parous mice had less unopposed nuclear ERα expression and increased levels of ERβ. These changes suggest that the nuclear expression of ERs dictates the proliferative nature of the breast and may explain the decreased breast cancer risk with parity.